Traditional warfarin (Coumadin) therapy usage experience on nonvalvular atrial fibrillation before non-Vitamin K antagonists (new oral anticoagulants) era from a center in Turkey - Emre Ozdemir; Ozgen Safak; Sadik Volkan Emren; Mehmet Serdar Bayata (International Journal of the Cardiovascular Academy, 2020)
Introduction: Atrial fibrillation (AF) is the most common arrhythmia with a prevalence that increases by aging. AF causes morbidity and mortality due to thromboembolic events. In developing countries, the use of new generation medications can be delayed. Objective: We evaluated nonvalvular AF patients without effective oral anticoagulation (OAC) when non- vitamin K antagonists (NOACs) were mostly unavailable in Turkey before 2012–2013. The results were compared with what would happen if NOAC was available in use. Patients and Methods: Two-hundred and five patients in AF with adequate information were detected 123 of these patients were nonvalvular AF, (92 patients in these 123 ones were not taking OAC or on ineffective INR range) were included in the study. Results: Thirty-one (25.2%) of these patients were already on effective warfarin therapy. Ninety-two (74.8%) patients were not on warfarin therapy or on out of effective therapeutic range. About 52.2% of participants were female. The mean age was 70.62 ± 11.8 years. Eighteen (19.5%) patients had a recurrent stroke. Conclusion: OACs are recommended for patients with high stroke risk according to CHA2DS2-VASc score. OAC therapy significantly decreases mortality, morbidity, and also especially stroke risk. The only OAC therapy was warfarin over the decades until NOACs have been found. In our study, if NOACs could be available before 2012 in Turkey, 74.8% of our cohort would be under the effective anticoagulation and 19.5% of patients may have avoided from stroke. This is important for patients' lives and also for their costs.